Numerical Modeling of the Blend Morphology Evolution in Twin‐Screw Extruders. Issue 3 (16th May 2022) - Wong, Wing‐Hin B.; de Bie, Vincent G.; Hulsen, Martien A.; Anderson, Patrick D.
Abstract : Front Cover : The disperse polymer blend morphology evolution is described using a macroscopic model, which clusters individual droplets in droplet populations. The blend model is used to perform a particle tracking simulation of the morphology evolution inside a twin‐screw extruder. The figure shows the size distribution of 1300 droplet populations along the cross‐section of a twin‐screw extruder. This is reported by Patrick D. Anderson and co‐workers in article number 2100087 .